Opinion mining and emotion recognition applied to learning environments. (15th July 2020) - Barrón Estrada, María Lucía; Zatarain Cabada, Ramón; Oramas Bustillos, Raúl; Graff, Mario
Highlights: Creation of two dataset for emotions and sentiments in text. Recognitions of learning-centered emotions in text. Comparison among machine & deep learning methods against an evolutionary approach. Integration of best classification model to an intelligent learning environment. Abstract: This paper presents a comparison among several sentiment analysis classifiers using three different techniques – machine learning, deep learning, and an evolutionary approach called EvoMSA – for the classification of educational opinions in an Intelligent Learning Environment called ILE-Java. To make this comparison, we develop two corpora of expressions into the programming languages domain, which reflect the emotional state of students regarding teachers, exams, homework, and academic projects, among others. A corpus called sentiTEXT has polarity (positive and negative) labels, while a corpus called eduSERE has positive and negative learning-centered emotions (engaged, excited, bored, and frustrated) labels. From the experiments carried out with the three techniques, we conclude that the evolutionary algorithm (EvoMSA) generated the best results with an accuracy of 93% for the corpus sentiTEXT, and 84% for the corpus eduSERE.